An introduction to international economics : new perspectives on the world economy - Reinert, Kenneth A. (Cambridge : Cambridge University Press, 2020)
This book is designed for a one-semester course in international economics, primarily targeting non-economics majors and programs in business, international relations, public policy, and development studies. It has been written to make international economics accessible to both students and professionals. Assuming a minimal background in economics and mathematics, the textbook goes beyond the usual trade-finance dichotomy to address international trade, international production, and international finance; and takes a practitioner point of view rather than a standard academic one, introducing students to the material needed to become effective analysts in international economic policy. This new edition features such additional topics as global production and global capital flows, migration, the Ricardian model, and international organizations like the IMF. Examples have been updated to include recent developments (Brexit, for example) and all charts include the latest data. The website for the text can be found at http://iie.gmu.edu.
Title from publisher's bibliographic system (viewed on 21 Sep 2020).
Keywords: elektronické knihy; electronic books; International economic relations; International trade; International finance